Motor learning and general adaptation syndrome - F. J. Moreno; E. M. Ordoño (Asociación Española de Ciencias del Deporte, 2010)
This work examines the General Adaptation Syndrome like a suitable framework to explain motor learning processes. Human motor behaviour is viewed like a complex system continuously interacting in the environment. Motor learning is proposed as an adaptation process to the tasks constraints. Training loads and practice load are also considered analogous. Practice is the vehicle of learning, but it must be applied with the enough amount of load to produce an adaptation to a new level of performance. The principles of sport training are presented related to motor learning topics. Common principles are proposed to explain the learning of motor skills, regardless of the level of complexity, and level of the performer, and providing basic criteria that should help to design learning tasks. Key Words:  Motor learning, adaptation, complex systems, training, motor skills.